TOTAL QUALITY MANAGEMENT (TQM) SEBAGAI STANDAR KUALITAS PENDIDIKAN - Isfiana Oktaria Nasihatul Umami; Prof. Dr. Muhammad Yasin, M.Pd (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
This article aims to analyse the implementation of Total Quality Management (TQM) principles in educational institutions, identify challenges and constraints in the implementation of TQM in educational institutions and provide strategic recommendations to improve the quality of education through the systematic and sustainable implementation of TQM. TQM is identified as an effective approach to improve the quality of education services to fulfil the expectations of society and stakeholders. The implementation of Total Quality Management (TQM) in improving the quality of education is in accordance with the 8 National Education Standards (SNP), namely the standards of content, process, graduate competence, teaching and education personnel, facilities and infrastructure, management, financing, and assessment. The research method used is qualitative, focusing on identifying and analysing the application of TQM principles in various educational institutions. Through a literature study, this article discusses how the application of Total Quality Management (TQM) principles can improve the quality of education in educational institutions, what are the challenges and obstacles faced by educational institutions in implementing TQM, and how strategies can be used to overcome obstacles in implementing TQM to improve the quality of education. The results of this study are that the implementation of TQM in educational institutions is proven to improve the quality of education through continuous improvement in the eight National Education Standards, Challenges in TQM Implementation are resistance to change, lack of management commitment, limited resources, and difficulty in measuring objective results. Strategies to overcome these obstacles require full commitment from all components of the organisation, continuous training, effective communication, and the development of an organisational culture that supports continuous improvement to overcome implementation challenges.